CONCEPTUAL PROFILE IN CHEMISTRY: THE MATTER OF ATOMIC THEORIES - Rezi Ulya Fauziah; Dian Novita (JCER (Journal of Chemistry Education Research), 2022)
The aim of the study was to analyse the conceptual profile in chemistry matter of atomic theories. An instrument of three-tier diagnostic test was given to 35 students from X Science 4 class in SMAN 1 Driyorejo and regarding to this worksheet treatment session was given to enhancing students achievement. This study shown the conceptual profile in chemistry varies in the reduction proportion value, but the lowest was Rutherford atomic theories with 0.48 in middle-category. The need of complementary views for the atomic structure expecially in atomic theories bring important issues for understanding and teaching chemistry, which will be discussed further in the article